Formation of Anthocyanin Ion-pairs. A Co-Pigmentation Effect - Figueiredo, Paulo (2012)
The influence of the addition of ionic salts (NaCI, NaBr, Nal, NaCIO,) on anthocyanin equilibria is studied in this work. The effect of their addition is a colour enhancement through the formation of an ion-pair between the charged flavylium cation and the anion, which displaces the equilibria towards the coloured flavylium form. The ion-pair formation is an alternative model to that which suggests a preferable hydration of salt anions instead of the flavylium cation. Throughout this work two natural anthocyanins are studied (malvidin 3,5-diglucoside and malvidin 3-glucoside) as well as one anthocyanidin (malvidin). The thermal and photochemical stability of the ion-pairs formed is also examined. Ex per i ments with a synthetic a n t h ocya n i n a na I og ue (4', 7 - d i h ydroxyf lavy I i u m c h lor ide) w h ic h has photochromic properties are also described for comparison purposes